2013
DOI: 10.1073/pnas.1215722110
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactam antibiotics modulate T-cell functions and gene expression via covalent binding to cellular albumin

Abstract: Recent work has suggested that beta-lactam antibiotics might directly affect eukaryotic cellular functions. Here, we studied the effects of commonly used beta-lactam antibiotics on rodent and human T cells in vitro and in vivo on T-cell–mediated experimental autoimmune diseases. We now report that experimental autoimmune encephalomyelitis and adjuvant arthritis were significantly more severe in rats treated with cefuroxime and other beta-lactams. T cells appeared to mediate the effect: an anti-myelin basic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…While the first report from 2011 was verified and germ free mice showed either complete resistance or attenuation of EAE in several experimental paradigms 4648 , using antibiotic cocktails to deplete gut microbiota has provided controversial results. Even though most of the antibiotic administration studies have shown an amelioration of EAE pointing to a disease promoting effect of gut bacteria 4951 , experimental evidence suggests that certain bacterial strains have a beneficial effect on EAE development and protect from exacerbated disease, as shown in treatment experiments using the macrolide antibiotics clarithromycine and azithromycin or the cephalosporine cefuroxime 52,53 .…”
Section: The Gut Microbiome and Dietary Factorsmentioning
confidence: 99%
“…While the first report from 2011 was verified and germ free mice showed either complete resistance or attenuation of EAE in several experimental paradigms 4648 , using antibiotic cocktails to deplete gut microbiota has provided controversial results. Even though most of the antibiotic administration studies have shown an amelioration of EAE pointing to a disease promoting effect of gut bacteria 4951 , experimental evidence suggests that certain bacterial strains have a beneficial effect on EAE development and protect from exacerbated disease, as shown in treatment experiments using the macrolide antibiotics clarithromycine and azithromycin or the cephalosporine cefuroxime 52,53 .…”
Section: The Gut Microbiome and Dietary Factorsmentioning
confidence: 99%
“…Interestingly, ceftriaxone has had no impact on the EAAT2 protein expression levels in several brain areas as well as on the glutamate uptake rate suggesting that in this model the positive effects of the antibiotic are not mediated through the modulation of glutamate concentration. Moreover, it seems that even the individual antibiotics within the β-lactam group may display differential immunomodulatory properties (Mor and Cohen, 2013). This mechanism operates via covalent binding of various β-lactams to cellular albumin and subsequent modulation of T cell function and gene expression.…”
Section: β-Lactamsmentioning
confidence: 99%
“…In this context, it is thought that some antibiotic compounds may directly stimulate the host immune system [16,17]. The current TB chemotherapy contains four first-line antibiotics namely, rifampicin, ethambutol, pyrazinamide and isoniazid.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to antibiotics, which are major therapeutic tools to promote further suppression of mycobacterial growth [13], host-targeted interventions have also been proposed as novel approaches to enhance control of TB [14,15]. In this context, it is thought that some antibiotic compounds may directly stimulate the host immune system [16,17] [27]. In that study, the authors have demonstrated a role for host autophagy as an essential requirement to the bactericidal activity of INH in H37Rv-infected murine macrophages.…”
mentioning
confidence: 99%